Development and in vitro evaluation of biomimetic injectable hydrogels from decellularized human nerves for central nervous system regeneration - Gopal Agarwal; Kennedy Moes; Christine E. Schmidt (Materials Today Bio)
Injuries to the central nervous system (CNS) often lead to persistent inflammation and limited regeneration. This study developed a clinically relevant injectable hydrogel derived from decellularized human peripheral nerves, with mechanical properties biomimicking native CNS tissue. Using a modified Hudson method, human sciatic nerves were decellularized, effectively removing immunogenic cellular debris while retaining the extracellular matrix. Two delipidation solvents, dichloromethane: ethanol (2:1 v/v) and n-hexane: isopropanol (3:1 v/v), were evaluated, with the former achieving optimal lipid removal and better digestion. The resulting solution was crosslinked with genipin, forming an injectable hydrogel (iHPN) that gelled within 12 min at 37 °C and exhibited mechanical stiffness of approximately 400 Pa. Human astrocytes, human microglial cell clone 3 (HMC3), and mouse RAW 264.7 macrophages were cultured individually within iHPN, with lipopolysaccharide (LPS) added to mimic CNS inflammation following injury. Compared to LPS-activated cells on tissue culture plates (TCP), astrocytes within iHPN maintained a quiescent state, as evidenced by reduced GFAP expression and IL-1β secretion. RAW 264.7 and HMC3 cells in iHPN displayed an anti-inflammatory phenotype, as shown by increased CD206 and decreased CD86/CD68 expression, along with higher IL-4 and lower TNF-α/IL-1β secretion. Human SH-SY5Y neuroblastoma cells exhibited higher viability and improved neuronal differentiation in iHPN compared to TCP. Human brain neurons had higher neuronal differentiation within iHPN compared to TCP or collagen hydrogels. Overall, iHPN is a novel injectable hydrogel that has potential for minimally invasive CNS applications, such as a carrier for cell or drug delivery and/or a biomaterial to support axonal growth.